Gadamer’s Hermeneutics and Literary Translation (London Journal of Research In Humanities and Social Sciences, 2026)
The aim of this article is to review some postulates of hermeneutics according to Hans-Georg Gadamer under the light of literary translation. The link between the hermeneutic cycle and literary translation is perhaps not so clear at first glance. However, at the heart of both processes (the interpretation of a text and the translation of a literary text) the phenomenon of comprehension is crucial. One cannot interpret or translate correctly what one does not understand. Moreover, the comprehension of a text is not limited to the comprehension of the words that comprise it. Truly understanding a text has implications that transcend mere textual exegesis; understanding something has political, ethical, and ideological implications, among others.
Keywords: Gadamer; hermeneutics.; interpretation; translation